Effects of dietary L-carnitine on growth performance of nursery pigs - Real, D.E.; Rincker, M.J.; Steidinger, M.E.; Carter, S.D.; Owen, K.Q.; Nelssen, Jim L.; Goodband, Robert D.; Tokach, Michael D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Four experiments were conducted to evaluate the effects of added dietary Lcarnitine on growth performance of nursery pigs. Pigs were fed a control diet containing no added L-carnitine or the control diet with 25, 50, 75, or 100 ppm of added L-carnitine (25, 50, or 100 ppm in Exp. 4). In Exps. 1, 2, and 3 for the overall study, ADG and F/G improved with increasing dietary L-carnitine. In Exp. 4, pigs fed increasing L-carnitine had improved ADG from d 0 to 3 and d 10 to 24. Increasing added carnitine improved F/G from d 10 to 24 and for the overall study. The results suggest that 25 to 50 ppm of added L-carnitine can improve ADG and F/G in nursery pigs. The largest response in pig growth performance was found when carnitine was supplemented to the phase II diet.
Keywords: Swine; Carnitine; Nursery pigs; B-vitamin